Mowj-e gowhar (Gem wave) composition and its history trend - سیّد علی محمّد سجادی; سیّد مهدی طباطبایی (تاریخ ادبیات)
The words of each combination must have certain similarities and proportions for companionship in order to be connected to each other through networks of imagination; For this reason, despite the old connection of some words in the Persian language and literature, in some cases this connection did not lead to the formation of a combination or if a combination was formed, it lasted for centuries. In this research, an attempt has been made to examine the historical process of the formation of the combination of Mowj-e Gowhar by reviewing the relationship between the two words Mowj (wave) and Gowhar (gem) in Persian poetry. A combination that is directly mentioned in almost 170 verses of Bedil's sonnets, and contemporary Bedil scholars, due to their insufficient understanding of it, have had problems in interpreting the verses. The necessity of historical study of the emergence of compounds and interpretations identifies the importance and necessity of this research, and the research method is based on following the historical process of the composition. The result of this research, in addition to getting the correct meaning of this interpretation, is to prove the historical connection in the formation of pairs of combinations and interpretations in Persian literature.